Search for the radiative Ξ−b → Ξ−γ decay; Journal of High Energy Physics; Vol. 2022, iss. 1 - Aaij R. Roel; Abdelmotteleb A. S.; Beteta C. A. Carlos Abellan; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich; Vagner A. R. Aleksandr Rudolfovich (2022, 2022)
Title screen